Kontrol Diskrit Hexapod dengan Metode Elman Neural Network dengan Studi Kasus Driving Simulator Game Sederhana - Lucky Leonardo Salim; Gregorius Satia Budhi; Felix Pasila (Jurnal Infra, 2017)
Game is one of many ways to get entertainment and to relief from stress. One of many category of game is simulation game where player can feel the effect of the gameplay. One of the many instrument that can help to get the effect of simulation is Diskrit Hexapod.The design of Diskrit Hexapod can be used in Driving Simulator with Arduino as its brain and controller for the Diskrit Hexapod. Diskrit Hexapod can move according to the visual display of the car in Driving Simulator game. Diskrit Hexapod can move accurately if receive the input of x-axis and z-axis from range -20° to 20° and y-axis from range -90° to 90°. The data used for the program is made of 161 pairs of inputs and has trained root-mean-squared-error of 0,0632